Evolution of Islamic Education Research Through a Comprehensive Bibliometric Review 2000–2024 - Judijanto, Loso (Westscience Press, 2026)
This study presents a comprehensive bibliometric review of research on Islamic education published between 2000 and 2024, aiming to map its intellectual structure, thematic evolution, and collaboration patterns over time. Using bibliometric techniques, data were extracted from the Scopus database and analyzed through performance indicators and science-mapping methods, including keyword co-occurrence, co-authorship, institutional affiliation, and country collaboration analyses. The results reveal that Islamic education research has been historically grounded, with strong emphasis on longitudinal and historical perspectives that form the core intellectual foundation of the field. Over time, the thematic focus has gradually shifted toward more interdisciplinary and applied concerns, particularly cultural contexts and contemporary educational practices. Collaboration analyses further show a dense but uneven global research network, dominated by Western institutions and countries, with emerging connections to Asia mediated through key bridging nations. The findings demonstrate that Islamic education research has evolved into a dynamic and diversified field, offering significant opportunities for future studies that emphasize cross-cultural perspectives, educational innovation, and broader global participation.